A note on resonant frequencies for a system of elastic wave equations - Luis A. Cortés-Vega (International Journal of Mathematics and Mathematical Sciences)
We present a rather simple proof of the existence of resonant frequencies for the direct scattering problem associated to a system of elastic wave equations with Dirichlet boundary condition. Our approach follows techniques similar to those in Cortés-Vega (2003). The proposed technique relies on a stationary approach of resonant frequencies, that is, the poles of the analytic continuation of the solution.